The Impact of Intelligent Delivery Systems and Automated Rail Logistics on the Efficiency and Safety of Clinical Item Transportation: A Observational Studies - Yi Li MN; Ping He BS; Xue-Lian Peng MN; Min Peng BS (Inquiry: The Journal of Health Care Organization, Provision, and Financing)
This paper aims to establish an intelligent delivery system integrated with track logistics and explores its impact on the clinical transportation of goods. The study analyzed hospital delivery items before and after the implementation of an intelligent delivery system combined with automated track logistics in 2023. Delivery conditions prior to the system’s activation served as the control group, while those post-implementation formed the observation group. This research assesses the effects on transportation efficiency, resource allocation, transport safety, and satisfaction among medical staff. The average delivery time of goods significantly decreased following the adoption of the intelligent delivery system combined with automated track logistics ( P  < .01). The total number of adverse delivery-related events was reduced from 25 to 4 ( P  < .01). Departmental medical staff reported substantial increases in scores for delivery efficiency, error incidence, and overall satisfaction with the delivery process ( P  < .01). The integration of the intelligent delivery system with automated track logistics significantly enhances the efficiency of clinical goods transportation, optimizes resource allocation, ensures the safe transport of items, and improves the patient experience and clinical staff satisfaction with delivery operations. Regular system maintenance and adjustments, supported by professional technical personnel, are essential to fully leverage the system's advantages.